Perlindungan Hukum terhadap Konsumen Parkir dalam Hal Terjadi Kehilangan di Area Parkir Lapangan Renon Kota Denpasar - Ida Bagus Kade Ari Dwi Putra (Jurnal Preferensi Hukum, 2020)
Consumer protection is an effort that is used to protect consumers, one of which is consumers of parking service consumers, so a Parking Area Company was established. The purpose of this study was to determine the Application of Regional Regulation No. 11 of 2005 concerning Parking Operational Systems in Denpasar City and the efforts of the Denpasar City Parking Area Company in protecting lost parking service users in the parking area of ​​Renon Field in Denpasar. This research uses an empirical juridical method with a sociological approach to law. Data collection methods used in this research are interview and literature study methods. The data in this study were sourced from primary and secondary data. The results of this study are there are still parking rates that do not comply with the provisions, there are still parking officers who collect parking in areas that have parking restrictions and there are still officers who do not want to serve consumers well. The effort of parking area companies in protecting consumers is by conducting evaluation activities every year, improving security services by holding parking attendant training every year and encouraging parking consumers to participate in protecting their luggage